Citrus Rootstock Propagation: Traditional Techniques and Recent Advances - Ute Albrecht; Lorenzo Rossi; Mongi Zekri (EDIS)
Commercially grown citrus trees are usually composed of two parts: 1) the scion, which is the aboveground portion of the tree that produces the fruit, and 2) the rootstock, which comprises the root system and the lower portion of the trunk. This new 4-page publication, chapter 6 of the forthcoming Citrus Nursery Production Guide, discusses three kinds of rootstock propagation: seed, cuttings, and tissue culture. Written by Ute Albrecht, Lorenzo Rossi, and Mongi Zekri and published by the UF/IFAS Horticultural Sciences Department. https://edis.ifas.ufl.edu/hs1329